EFFECT OF TILLAGE AND WEED MANAGEMENT PRACTICES ON WEED DYNAMICS, YIELD ATTRIBUTES AND YIELD OF MAIZE IN SOUTHERN TELANGANA ZONE - SURENDRA BABU. P; TRIVENI. S, KIRAN KUMAR REDDY. K, VANI. K. P, SUDHAKAR. C (The Journal of Research, PJTSAU, 2023)
Conservation Agriculture (CA) is an alternative sustainable production system to the conventional tillage system for resource conservation in rainfed agriculture. Weed management is the major constraint for the adoption of CA in rainfed regions. A two years study was conducted at Agricultural Research Station, Tandur, during two consecutive kharif seasons of 2018 and 2019 to investigate the effect of tillage and weed management practices on weed dynamics, yield attributes and yield of maize in the Southern Telangana Zone. The experiment was carried out in strip-plot design with tillage methods assigned to vertical plots and weed management practices allotted to horizontal plots which were replicated thrice. It was observed that there is no significant difference between tillage methods but weed management practices significantly influenced weed density, weed dry weight, yield attributes and yield. The findings revealed that conventional tillage and hand weeding twice at 20 and 40 DAS maintained the weed density and weed dry weight below the economic threshold level and enhanced the yield of maize in clay loam soils under rainfed conditions. The interaction effect of tillage and weed management practices was found to be non-significant.